Challenges and opportunities for ports in achieving net-zero emissions in maritime transport - Pramithodha Halpe; Michelle Adams; Tony R. Walker (Transportation Research Interdisciplinary Perspectives)
Shipping ports are vital nodes in maritime transport networks and play crucial roles in the global economy and international trade. Despite their economic importance ports have adverse effects on the environment. Air pollution and emissions of greenhouse gases (GHGs) are of great concern since the maritime industry accounts for 2–3% of global GHG emissions. The shipping industry is projected to grow on average at 2.1% annually for the next four years and is under enormous pressure from stakeholders and the International Maritime Organization (IMO) to curb GHG emissions to align with the Paris Agreement. The IMO strategy to cut GHG emissions from international shipping aims for a reduction of 20%, by 2030, and 70% by 2040, with respect to 2008 and achieve 100% reduction by 2050 to achieve net-zero emissions. The aim of this study was to investigate the role of shipping ports in overcoming challenges and maximizing opportunities to achieve net-zero emissions in maritime transport. Based on the existing literature from the past decade, this study highlights the magnitude of the problem, the challenges the sector is facing in terms of economic, technological and policy implications in achieving net-zero emissions. This perspective study offers potential solutions and opportunities for ports to achieve net-zero targets by improving infrastructure development, facilitating vessel emissions reduction, adoption of low-emission fuels, renewable energy adoption, and implementing green shipping corridors.